A phenomenological study of Jordanian women's experience of sexual intercourse after giving birth. (September 2020) - Alnuaimi, Karimeh; Obeisat, Salwa; Almalik, Mona; Ali, Reem; Alshraifeen, Ali
Highlights: In a conservative culture sexuality is a sensitive issue that is often not discussed by health-care professionals (HCPs) with women in the postpartum period. This study explored Jordanian women's experiences about sexual relationships after giving birth and provided a detailed and in-depth understanding of women's needs and suggested improvements in care. Women enduring sexual discomforts after giving birth, which might become a health problem and difficult to treat after giving birth, however, they do not receive adequate sexual education from healthcare professionals (HCPs). Abstract: Aim: to explore the sexual experiences of Jordanian women on the first occasion after giving birth. Methods: phenomenological qualitative research. Twenty-five Jordanian women were purposively recruited from two maternal health centres and interviewed. Findings: four themes emerged: "culture and religion v/s health professionals in resumption of sexual intercourse"; "enduring physical and psychological discomforts"; "husbands' role in resumption of sexual intercourse"; and "newborn babies' role in the experience of sexual intercourse". Conclusion: health professionals need to adopt appropriate maternal clinical guidelines to meet women's needs. There is a need to give greater emphasis on sexual health care provided to women during pregnancy and after giving birth.